2009
DOI: 10.1007/s00415-009-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of the circle of Willis, direction of flow, and shape of the aneurysm as risk factors for rupture of intracranial aneurysms

Abstract: Direction of flow into the aneurysm and nonspherical (both elliptical and multilobed) shape may contribute to the risk of rupture, but are related to aneurysm size and may warrant more frequent follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 10 publications
(30 reference statements)
2
62
1
Order By: Relevance
“…Furthermore, a dominant A1 has previously been identified as a potential risk factor for both aneurysm formation and rupture. 1,4 Kwak et al reported the incidence of single A1 vessel dominance in patients with AcomA aneurysms to be as high as 68% (145 of 213). 2 That study, among others, defined hypoplasia as an A1 less then half the diameter of the dominant side when comparing left and right A1 segments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a dominant A1 has previously been identified as a potential risk factor for both aneurysm formation and rupture. 1,4 Kwak et al reported the incidence of single A1 vessel dominance in patients with AcomA aneurysms to be as high as 68% (145 of 213). 2 That study, among others, defined hypoplasia as an A1 less then half the diameter of the dominant side when comparing left and right A1 segments.…”
mentioning
confidence: 99%
“…2 That study, among others, defined hypoplasia as an A1 less then half the diameter of the dominant side when comparing left and right A1 segments. 2,3,5 Other studies have defined hypoplasia as a greater than one-third difference between left and right A1 diameters 4 or a vessel diameter of Յ1 mm. 6 This multiplicity and variance of definitions make the associations identified within these studies challenging to compare.…”
mentioning
confidence: 99%
“…There are many studies proposing better aneurysm parameters for rupture aneurysm status (aneurysm height, aneurysm width, aspect ratio, bottleneck ratio, size ratio, aneurysm inclination angle, parent vessel diameter etc.). Irregular shape is found more often in ruptured aneurysms [11][12][13]. Previous studies on aneurysm inclination angle showed different results from insignificant to strongly significant odds ratios [7,[14][15][16].…”
Section: Discussionmentioning
confidence: 89%
“…): size (largest diameter in millimeters), 20 aspect ratio (height divided by the neck size), 21 and spheric or nonspheric nature of the aneurysm ("spheric" defined as an aneurysm height within 80%-125% of its width). 20 Quantitative hemodynamic parameters (mean wall shear stress, maximum wall shear stress, and oscillatory shear index) were derived from the hemodynamic data provided by CFD by using in-house-developed software. The quantitative hemodynamic parameters were derived from the surface of the aneurysm sac.…”
Section: Quantitative Parameter Assessmentmentioning
confidence: 99%